RURAL AREAS OF ARAGATSOTN REGION: THE POPULATION AND SETTLEMENTS (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
It is analyzed in this article the main preconditions of the formation of the rural areas and rural population of Aragatsotn region. It has been revealed the dynamics of rural areas and population trends according to altitude zones and overpopulation factors.
Keywords: Aragatsotn Region; rural areas; rural settlements; rural population; dynamics of population and settlements